Lifetimes and g-factors of the 6− and 7− isomers in 66Ga and 68Ga - Filevich, A.; Ceballos, A.; Mariscotti, M. A. J; Thieberger, P.; Der Mateosian, E. (Elsevier B.V., 1978)
Fil: Filevich, A. Comisión Nacional de Energía Atómica; Argentina